Investigation of the mechanical, thermal, and morphological properties of isotactic polypropylene/linear low-density polyethylene/ethylene vinyl acetate polymer blends and their fibers. (March 2016) - Kocak, Dilara; Akalin, Mehmet; Merdan, Nigar
In order to improve the functionality of certain defective characteristics of polypropylene polymer and fiber, their blends are analyzed physically and chemically both in the industry and the academia. There are fibers obtained from two different polymer blends and additive-added fibers in the polypropylene fiber industry. The aim of this study is to obtain polymer blends and their fibers, which consist of isotactic polypropylene and linear low-density polyethylene. In order to improve the blending of isotactic polypropylene and linear low-density polyethylene, ethylene vinyl acetate was added in the blend at different concentration such as 1, 5, 10, and 15% by using a twin-screw extruder. Polymer blends and their fibers were produced from the blends with different ratios of blending. Besides, the mechanical properties including strength, elongation, modulus of elasticity, yield of strength, Izod impact strength, hardness, thermal properties (differential scanning calorimetry and melt flow index), and morphological properties (scanning electron microscopy) of polymer blends and their fibers were investigated.